The condition of the leukocyte section of cellular mechanisms of adaptation under the influence of emotional load for operators of passenger electric transport due to the professional activities - V. I. Gorsha (Kazimierz Wielki University, 2017)
Gorsha V. I. The condition of the leukocyte section of cellular mechanisms of adaptation under the influence of emotional load for operators of passenger electric transport due to the professional activities. Journal of Education, Health and Sport. 2016;6(11):741-748. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.252486 http://ojs.ukw.edu.pl/index.php/johs/article/view/4181         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016.   The condition of the leukocyte section of cellular mechanisms of adaptation under the influence of emotional load for operators of passenger electric transport due to the professional activities   V. I. Gorsha   Ukrainian Research Institute of Transport Medicine of the Ministry of Health of Ukraine   Summary A total of 114 drivers of passenger electric transport and 27 people who didn't have the high level emotional load due to the professional activities were examined. According to the blood leukogram of drivers was identified more lower levels of leukocytes and higher levels of eosinophils comparing with the control group (respectively - p = 0.00937 and p = 0.04149). Registered changes are evidence of the reduction of cellular immune defenses mechanisms and allergic activation for the drivers of passenger electric transport. The general condition of adaptation for cellular reactions was much worse for the passengers drivers of electric transport unlike the employees without emotional load, that determined of a significant increases of the failures state of compensation mechanisms and reducing of adaptation - 38.6% (for employees without emotional load - 7.4%) and the same reducing of conditions satisfactory adaptation - 61.4% (for employees without emotional burden - 92.6%) Key words: the drivers of passenger electric transport, emotional load, cellular mechanisms of adaptation.